2005
DOI: 10.5551/jat.12.338
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Lipid Management in 1,836 Patients with Coronary Artery Disease: A multicenter survey to evaluate the percentage of Japanese coronary artery disease patients achieving the target low-density lipoprotein cholesterol level specified by the Japan Atherosclerosis Society

Abstract: To determine the status of lipid management in patients with coronary artery disease (CAD) in Japan, we assessed CAD patients who had been receiving lipid-lowering therapy for six months in a cross-sectional survey conducted between June 2001 and December 2002. We defined the achievement rate as the percentage of patients who achieved the target LDL-C level (< 100 mg/dl) specified by the Japan Atherosclerosis Society (JAS). A total of 1,836 Japanese CAD patients were enrolled. In total, 549 (29.9%) achieved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…The rate of statin therapy was higher than the result in Japan (36.3%). 27 A study of Hong Kong showed only 37% of the participants received the lipid lowering drugs. 28 Cooke and Hammerash's study reported lipid lowering therapy was only prescribed to 68.6% of their patients, with no significant sex differences (men vs women, 71.4% vs 63.3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of statin therapy was higher than the result in Japan (36.3%). 27 A study of Hong Kong showed only 37% of the participants received the lipid lowering drugs. 28 Cooke and Hammerash's study reported lipid lowering therapy was only prescribed to 68.6% of their patients, with no significant sex differences (men vs women, 71.4% vs 63.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Reports showed the rate of achieving the target in patients with coronary heart disease was 29.9% in Japan 27 and 15% in Hong Kong. 28 Cooke and Hammerash's study indicted of the patients prescribed lipid lowering therapy (primarily statins), 53.8% of them achieved target (LDL-C of <2.60 mmol/L).…”
Section: Resultsmentioning
confidence: 99%
“…Ezetimibe is effective as monotherapy 1,2) and is more potent in combination with HMG-CoA reductase inhibitors (statins), such as simvastatin 3) , lovastatin 4) , pravastatin 5) , and atorvastatin 6) . Recent study revealed that patients with coronary artery disease should be treated more strictly 7,8) . The activity of LDL receptors is enhanced by statins, which have almost no effect on the plasma cholesterol concentration of homozygous familial hypercholesterolemic patients because of the patients' total lack of LDL receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 148 patients in the present study, therefore, 65 patients (45 men, 20 women) received statins after CAG, and 83 (62 men, 21 women) did not receive statins after CAG. The statins administered to patients consisted of atorvastatin, fluvastatin, simvastatin, and pravastatin 12) .…”
Section: Introductionmentioning
confidence: 99%